Contradictions hindering the provision of mental healthcare and psychosocial services to women experiencing homelessness in Addis Ababa, Ethiopia: service providers’ and programme coordinators’ experiences and perspectives - Kalkidan Yohannes; Yemane Berhane; Hannah Bradby; Sibylle Herzig van Wees; Mats Målqvist (BMC Health Services Research, 2023)
Abstract Background Mental health conditions are among the health issues associated with homelessness, and providing mental healthcare to people experiencing homelessness is challenging. Despite the pressing issue of homelessness in Addis Ababa, Ethiopia, there is scant research on how service providers address women’s mental health and psychosocial needs. Therefore, we explored service providers’ and programme coordinators’ perceptions and experiences regarding mental healthcare and psychosocial services delivery to women experiencing street homelessness in the city. Methods We conducted a descriptive qualitative study with selected healthcare and social support providers and programme coordinators. The study involved 34 participants from governmental and non-governmental organisations in Addis Ababa, Ethiopia. Data were analysed using an inductive thematic approach. Results Four themes were derived from the analysis. The first of these was “divergent intentions and actions”. While service providers and programme coordinators showed empathy and compassion, they also objectified and blamed people for their own homelessness. They also expressed opposing views on mental health stigma and compassion for these people. The second theme addressed “problem-solution incompatibility”, which focused on the daily challenges of women experiencing homelessness and the types of services participants prioritised. Service providers and programme coordinators proposed non-comprehensive support despite the situation’s complexity. The participants did not emphasise the significance of gender-sensitive and trauma-informed care for women experiencing street homelessness in the third theme, “the lack of gendered and trauma-informed care despite an acknowledgement that women face unique challenges”. The fourth theme, “mismatched resources,” indicated structural and systemic barriers to providing services to homeless women. Conclusions Conflicting attitudes and practices exist at the individual, organisational, and systemic levels, making it challenging to provide mental healthcare and psychosocial services to women experiencing homelessness. An integrated, gender-sensitive, and trauma-informed approach is necessary to assist women experiencing homelessness.